THE ROLE OF CUSTOMER SATISFACTION IN INCREASING SALES IN THE SERVICE SECTOR - HACIYEV, Nicat (Annals of Spiru Haret University. Economic Series, 2019)
This paper’s aim is to explain the role of customer satisfaction in service sector, especially in hotel and bank industries and the ways in which customer satisfaction can be measured and increased. Customer satisfaction is the key factor that determines the future sales of the company. This paper provides detailed information on how customer satisfaction affects and can be increased in bank and hotel industries. In order to explain it, the paper contains information about SERVQUAL Method for explaining customer expectations in five measurements such as reliability, responsiveness, assurance, empathy and tangibles; and 5 Gaps regarding hotel industry and Service Profit Chain for bank industry. [Arlen, 2008] The study supports understanding customers, having an individual approach to each of them, keeping good relationships with them and with keeping customer satisfaction in high level increase sales.